Motor-Sparing Nerve Blocks Can Improve the Results of Digit Tendon Surgery: A Case Report. Issue 2 (14th February 2022) - Van Herreweghe, Imré; Caekebeke, Pieter; Balocco, Angela Lucia; Van Boxstael, Sam; Hadzic, Admir
Abstract : A 56-year-old woman presented with flexion dysfunction of the fifth digit 6 weeks after surgical repair of a flexor digitorum profundus laceration. She was scheduled for surgical adhesiolysis and restoration of the functionality of the finger. Intraoperative monitoring of the range of motion by active flexion was deemed important to prevent incomplete release of the tendon and residual dysfunction. Distal median and ulnar nerve blocks were used for anesthesia with the patient's ability to flex the finger. This case suggests that motor-sparing peripheral nerve blocks can improve functional outcome in certain hand surgeries.